How do massive primordial black holes impact the formation of the first stars and galaxies? - Zhang, Saiyang; Liu, Boyuan; Bromm, Volker; Jeon, Junehyoung; Boylan-Kolchin, Michael; Kühnel, Florian (The astrophysical journal, 2025)
We investigate the impact of massive primordial black holes (PBHs; mBH ∼ 106 M⊙) on the star formation and first galaxy assembly process using high-resolution hydrodynamical simulations from z = 1100 to z ∼ 9. We find that PBH accretion is self-regulated by feedback, suppressing mass growth unless feedback is weak. PBHs accelerate structure formation by seeding dark matter (DM) halos and gravitationally attracting gas, but strong feedback can delay cooling and suppress star formation. In addition, the presence of baryon-DM streaming creates an offset between the PBH location and the peaks induced in gas density, promoting earlier and more efficient star formation compared to standard ΛCDM. By z ∼ 10, PBH-seeded galaxies form dense star clusters, with PBH-tostellar mass ratios comparable to observed high-z active galactic nuclei like UHZ-1. Our results support PBHs as viable supermassive black hole (SMBH) seeds but do not exclude alternative scenarios. We emphasize that PBHseeding provides a natural explanation for some of the newly discovered overmassive SMBHs at high redshift, in particular those with extreme ratios of BH-to-dynamical (virial) mass that challenge standard formation channels. Future studies with ultra-deep JWST surveys, the Roman Space Telescope, and radio surveys with facilities such as the Square Kilometre Array and Hydrogen Epoch of Reionization Array will be critical in distinguishing PBHdriven SMBH growth from other pathways.
Gesehen am 20.01.2026